A high-entropy hydroxyl oxide for water electrolysis and its preparation method

High-entropy hydroxy oxides were prepared by hydrothermal deposition and electrochemical reconstruction, which solved the problem of high cost of water electrolysis catalysts, achieved efficient and stable water electrolysis catalytic performance, reduced electrode preparation cost, and has good potential for industrial application.

CN117023659BActive Publication Date: 2025-11-14WUXI HUAGUANG BOILER +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311085530.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-28
Publication Date
2025-11-14
Estimated Expiration
2043-08-28

AI Technical Summary

Technical Problem

Existing water electrolysis catalysts are expensive and scarce, precious metal catalysts are limited in large-scale applications, and the oxygen evolution reaction has a high overpotential, resulting in a low reaction rate.

Method used

High-entropy hydroxy oxides were prepared using a hydrothermal deposition coupled with electrochemical reconstruction method. By growing co-hydroxy oxides of Fe, Co, Ni, Cu and Mo in situ on a metal support, a highly disordered high-entropy material was formed, providing a large number of active sites and synergistic effects, thereby reducing the cost of electrode fabrication.

Benefits of technology

It achieves efficient and stable catalytic performance in water electrolysis, significantly reduces electrode preparation costs, and has good potential for industrial application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117023659B_ABST
    Figure CN117023659B_ABST
Patent Text Reader

Abstract

This invention belongs to the field of water electrolysis application technology, and relates to a high-entropy hydroxy oxide for water electrolysis and its preparation method. It can be used in the field of alkaline water electrolysis and has a significant catalytic effect on hydrogen production from alkaline water electrolysis, greatly reducing the cost of electrode preparation. It is prepared by hydrothermal deposition coupled with electrochemical reconstruction to obtain a watermelon seed-shaped co-hydroxy oxide of Fe, Co, Ni, Cu and Mo with a thickness of 0.3-1.0 μm. The specific steps of the hydrothermal deposition coupled with electrochemical reconstruction preparation method are as follows: Step (1): A certain amount of iron salt, cobalt salt, nickel salt, copper salt and citric acid are added to a mixed solution of water and ethanol. Under stirring, an aqueous solution of molybdate is added, and a molybdenum-based composite oxide is obtained by hydrothermal deposition. Step (2): The molybdenum-based composite oxide obtained in step (1) is subjected to electrochemical treatment. The molybdenum-based composite oxide is electrochemically reconstructed into a high-entropy hydroxy oxide, named FeCoNiCuMoOOH.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of water electrolysis application technology, and relates to a high-entropy hydroxyl oxide for water electrolysis and its preparation method. Background Technology

[0002] The escalating energy crisis and environmental problems are forcing the world to seek sustainable and renewable energy sources. Hydrogen, with its high energy density (140 MJ / kg) and zero carbon dioxide emissions, is considered one of the most promising clean energy sources of the 21st century. Electrochemical water splitting for hydrogen production has been widely recognized as the most attractive method for obtaining clean fuels from renewable energy sources. Electrochemical water splitting involves two half-reactions: the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER). The OER is a four-electron transfer reaction that requires a high overpotential, significantly reducing the overall reaction rate and becoming the bottleneck for hydrogen production from water electrolysis. Noble metal catalysts, such as Ir / Ru, are considered to be the most efficient OER electrocatalysts to date. However, the high cost and scarcity of noble metals have limited their widespread application in large-scale development. This necessitates efficient, stable, and inexpensive OER catalysts to reduce the high overpotential and accelerate the reaction. First-row transition metal (such as Ni, Co, Fe)-based catalysts, especially transition metal oxides or (oxy)hydrides, have attracted widespread attention due to their excellent catalytic activity, abundance, stability, and environmental friendliness. High-entropy materials typically exhibit effects distinct from traditional materials, including sluggish diffusion and the cocktail effect. Due to their exceptional electrochemical properties, they are considered potential materials for catalytic oxidation-reduction processes (OERs) and are currently a major research focus in the international materials science community. Because of their high configurational entropy, high-entropy materials often possess highly disordered structures and random distributions of multiple components. This highly disordered structure can lead to a high density of defects, and even coordinated unsaturated sites, meaning they can provide a large number of accessible active sites for OERs. The random distribution of multiple components results in significant homogeneity, generating synergistic effects that promote interatomic interactions and alter electronic structures, thereby influencing intrinsic activity. Furthermore, the entropy stabilization effect can effectively improve the robustness of high-entropy materials in electrochemical processes. Summary of the Invention

[0003] To address the high cost of existing water electrolysis catalysts, this invention provides a high-entropy hydroxyl oxide for water electrolysis and its preparation method. This oxide can be used in alkaline water electrolysis and exhibits significant catalytic activity for hydrogen production from alkaline water electrolysis, thereby greatly reducing the cost of electrode preparation.

[0004] The technical solution of the present invention:

[0005] A high-entropy hydroxyl oxide for water electrolysis is prepared by hydrothermal deposition coupled with electrochemical reconstruction to obtain a watermelon seed-like co-hydroxyl oxide of Fe, Co, Ni, Cu and Mo with a thickness of 0.3-1.0 μm. The specific steps of the hydrothermal deposition coupled with electrochemical reconstruction preparation method are as follows:

[0006] Step (1): Add a certain amount of iron salt, cobalt salt, nickel salt, copper salt, and citric acid to a mixed solution of water and ethanol. Add an aqueous solution of molybdate under stirring, and then transfer it to a hydrothermal reactor and keep it at 120-160℃ for 18-36 hours. After cooling to room temperature, wash and dry to obtain powdered molybdenum-based composite oxide, named FeCoNiCuMoOx. If a metal support is present during hydrothermal deposition, in-situ grown molybdenum-based composite oxide on the metal support can be obtained.

[0007] Step (2): The molybdenum-based composite oxide obtained in step (1) is subjected to electrochemical treatment using a strongly alkaline solution as the electrolyte, and a voltage of 1.4-5 V or higher than 10 mA cm⁻¹ relative to the reversible hydrogen electrode is applied. -1 When a current density is applied and held for a certain period of time, the molybdenum-based composite oxide is electrochemically reconstructed into a high-entropy hydroxy oxide, named FeCoNiCuMoOOH.

[0008] Furthermore, in step (1), the reactants, iron salt, cobalt salt, nickel salt, copper salt, and molybdate are in equal proportion or one of them is in excess / deficient by 20%, and the molar amount of citric acid accounts for 20-40% of the total molar amount.

[0009] The metal carrier mentioned in step (1) is a foam material or wire mesh material of cobalt, nickel, or copper; when a cobalt, nickel, or copper matrix is ​​used, the metal salt of the corresponding matrix can be reduced or not fed at all, and Fe with a high redox potential 3+ It will oxidize the metal atoms on the surface of the substrate into metal ions to participate in precipitation.

[0010] The molybdenum-based composite oxide described in step (1) mainly comprises: Fe2(MoO4)3, Co2Mo3O8, NiFe2O4, Cu2O and Fe3O4.

[0011] The beneficial effects of this invention are as follows: The preparation method of the high-entropy hydroxyl oxide in this invention is simple, the raw materials are inexpensive and readily available, and it has excellent water decomposition performance and stability when used in alkaline water electrolysis, which has great potential for industrial application. It realizes the preparation of highly stable and high-performance electrodes, greatly reduces the cost of electrode preparation, and is conducive to the popularization and application of water electrolysis hydrogen production technology. Attached Figure Description

[0012] Figure 1 and Figure 2Scanning electron microscope image of the high-entropy hydroxyl oxide prepared for Example 1.

[0013] Figure 3 OER polarization curves of the high-entropy hydroxyl oxides prepared for Example 1 and Comparative Examples 1-3. Detailed Embodiments

[0014] The following embodiments are provided to better understand the present invention and are not limited to the preferred embodiments described. They do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, is within the scope of protection of the present invention.

[0015] Comparative Example 1

[0016] Step (1): Add 4 mmol of ferric nitrate nonahydrate, 4 mmol of copper nitrate trihydrate, and 10 mmol of citric acid monohydrate to a mixed solution of water and ethanol (V / V = 15 ml / 15 ml). While stirring vigorously, add 20 ml of an aqueous solution of 4 mmol of sodium molybdate dihydrate, and then add 3 cm × 5 cm nickel foam to the solution. The solution is then transferred to a hydrothermal reactor and kept at 140 °C for 24 hours. After cooling to room temperature, wash and dry to obtain FeNiCuMoOx / NF.

[0017] Step (2): The FeNiCuMoOx / NF obtained in step (1) was subjected to electrochemical treatment. A three-electrode system was formed with 1 M KOH solution as electrolyte, platinum sheet as counter electrode, Hg / HgO as reference electrode, and FeNiCuMoOx / NF as working electrode. The material was reconstructed into FeNiCuMoOOH / NF by 80 voltammetric cycles (CV) in the voltage range of 0.3-0.8V vs. Hg / HgO.

[0018] Comparative Example 2

[0019] Step (1): Add 4 mmol of ferric nitrate nonahydrate, 4 mmol of cobalt nitrate hexahydrate, and 10 mmol of citric acid monohydrate to a mixed solution of water and ethanol (V / V = 15 ml / 15 ml). While stirring vigorously, add 20 ml of an aqueous solution of 4 mmol of sodium molybdate dihydrate, and then add 3 cm × 5 cm nickel foam to the solution. The solution is then transferred to a hydrothermal reactor and kept at 140 °C for 24 hours. After cooling to room temperature, wash and dry to obtain FeCoNiMoOx / NF.

[0020] Step (2): The FeCoNiMoOx / NF obtained in step (1) was subjected to electrochemical treatment. A three-electrode system was formed with 1 M KOH solution as electrolyte, platinum sheet as counter electrode, Hg / HgO as reference electrode, and FeCoNiMoOx / NF as working electrode. The material was reconstructed into FeCoNiMoOOH / NF by 80 voltammetric cycles (CV) in the voltage range of 0.3-0.8V vs. Hg / HgO.

[0021] Comparative Example 3

[0022] Step (1): 4 mmol cobalt nitrate hexahydrate, 4 mmol nickel nitrate hexahydrate, 4 mmol copper nitrate trihydrate, and 10 mmol citric acid monohydrate were added to a mixed solution of water and ethanol (V / V = 15 ml / 15 ml). Under vigorous stirring, 20 ml of an aqueous solution of 4 mmol sodium molybdate dihydrate was added, followed by the addition of 3 cm × 5 cm nickel foam. The solution was then transferred to a hydrothermal reactor and maintained at 140 °C for 24 hours. After cooling to room temperature, the solution was washed and dried to obtain CoNiCuMoOx / NF.

[0023] Step (2): The CoNiCuMoOx / NF obtained in step (1) was subjected to electrochemical treatment. A three-electrode system was formed with 1 M KOH solution as electrolyte, platinum sheet as counter electrode, Hg / HgO as reference electrode, and CoNiCuMoOx / NF as working electrode. The material was reconstructed into CoNiCuMoOOH / NF by 80 voltammetric cycles (CV) in the voltage range of 0.3-0.8V vs. Hg / HgO.

[0024] Example 1

[0025] The preparation method of a high-entropy hydroxyl oxide for water electrolysis has the following steps:

[0026] Step (1): 4 mmol ferric nitrate nonahydrate, 4 mmol cobalt nitrate hexahydrate, 4 mmol copper nitrate trihydrate, and 10 mmol citric acid monohydrate were added to a mixed solution of water and ethanol (V / V = 15 ml / 15 ml). Under vigorous stirring, 20 ml of an aqueous solution of 4 mmol sodium molybdate dihydrate was added, followed by the addition of 3 cm × 5 cm nickel foam. The solution was then transferred to a hydrothermal reactor and maintained at 140 °C for 24 hours. After cooling to room temperature, the solution was washed and dried to obtain FeCoNiCuMoOx / NF.

[0027] Step (2): The FeCoNiCuMoOx / NF obtained in step (1) was subjected to electrochemical treatment. A three-electrode system was formed with 1 M KOH solution as electrolyte, platinum sheet as counter electrode, Hg / HgO as reference electrode, and FeCoNiCuMoOx / NF as working electrode. The material was reconstructed into FeCoNiCuMoOOH / NF by 80 voltammetric cycles (CV) in the voltage range of 0.3-0.8V vs. Hg / HgO.

[0028] Example 2

[0029] The preparation method of a high-entropy hydroxyl oxide for water electrolysis has the following steps:

[0030] Step (1): 4 mmol ferric nitrate nonahydrate, 4 mmol cobalt nitrate hexahydrate, 4 mmol nickel nitrate hexahydrate, and 10 mmol citric acid monohydrate were added to a mixed solution of water and ethanol (V / V = 15 ml / 15 ml). Under vigorous stirring, 20 ml of an aqueous solution of 4 mmol sodium molybdate dihydrate was added, followed by the addition of 3 cm × 5 cm copper foam. The solution was then transferred to a hydrothermal reactor and maintained at 140 °C for 24 hours. After cooling to room temperature, the solution was washed and dried to obtain FeCoNiCuMoOx / NF.

[0031] Step (2): The FeCoNiCuMoOx / NF obtained in step (1) was subjected to electrochemical treatment. A three-electrode system was formed with 1 M KOH solution as electrolyte, platinum sheet as counter electrode, Hg / HgO as reference electrode, and FeCoNiCuMoOx / NF as working electrode. The system was maintained at a constant voltage of 1.0 V vs. Hg / HgO for 4 hours, and the material was reconstructed into FeCoNiCuMoOOH / NF.

[0032] Example 3

[0033] The preparation method of a high-entropy hydroxyl oxide for water electrolysis has the following steps:

[0034] Step (1): 4 mmol ferric nitrate nonahydrate, 3 mmol cobalt nitrate hexahydrate, 4 mmol copper nitrate trihydrate, and 10 mmol citric acid monohydrate were added to a mixed solution of water and ethanol (V / V = 15 ml / 15 ml). Under vigorous stirring, 20 ml of an aqueous solution of 4 mmol sodium molybdate dihydrate was added, followed by the addition of 3 cm × 5 cm nickel foam. The solution was then transferred to a hydrothermal reactor and maintained at 140 °C for 24 hours. After cooling to room temperature, the solution was washed and dried to obtain FeCoNiCuMoOx / NF.

[0035] Step (2): The FeCoNiCuMoOx / NF obtained in step (1) was subjected to electrochemical treatment. A three-electrode system was formed using 1 M KOH solution as the electrolyte, a platinum sheet as the counter electrode, Hg / HgO as the reference electrode, and FeCoNiCuMoOx / NF as the working electrode. The electrolyte was then subjected to electrochemical treatment at 80 mAcm. -1 After being held at a constant current density for 3 hours, the material was reconstructed to FeCoNiCuMoOOH / NF.

[0036] Example 4

[0037] The preparation method of a high-entropy hydroxyl oxide for water electrolysis has the following steps:

[0038] Step (1): 4 mmol ferric nitrate nonahydrate, 4 mmol cobalt nitrate hexahydrate, 4 mmol nickel nitrate hexahydrate, 4 mmol copper nitrate trihydrate, and 10 mmol citric acid monohydrate were added to a mixed solution of water and ethanol (V / V = 15 ml / 15 ml). Then, 20 ml of an aqueous solution of 4 mmol sodium molybdate dihydrate was added under vigorous stirring. The solution was then transferred to a hydrothermal reactor and kept at 140 °C for 24 hours. After cooling to room temperature, the solution was washed, centrifuged, and dried to obtain FeCoNiCuMoOx.

[0039] Step (2): The FeCoNiCuMoOx obtained in step (1) is subjected to electrochemical treatment. A three-electrode system is formed with 1 M KOH solution as electrolyte, platinum sheet as counter electrode, Hg / HgO as reference electrode, and FeCoNiCuMoOx as working electrode. The material is reconstructed into FeCoNiCuMoOOH by 80 voltammetric cycles (CV) in the voltage range of 0.3-0.8V vs. Hg / HgO.

[0040] Example 5

[0041] The preparation method of a high-entropy hydroxyl oxide for water electrolysis has the following steps:

[0042] Step (1): 4 mmol ferric nitrate nonahydrate, 4 mmol cobalt nitrate hexahydrate, 4 mmol nickel nitrate hexahydrate, 4 mmol copper sulfate pentahydrate, and 13.8 mmol citric acid monohydrate were added to a mixed solution of water and ethanol (V / V = 15 ml / 15 ml). Then, 20 ml of an aqueous solution of 4.8 mmol sodium molybdate dihydrate was added under vigorous stirring. The solution was then transferred to a hydrothermal reactor and maintained at 140 °C for 24 hours. After cooling to room temperature, the solution was washed and dried to obtain FeCoNiCuMoOx.

[0043] Step (2): The FeCoNiCuMoO obtained in step (1) was subjected to electrochemical treatment. A three-electrode system was formed with 1 M KOH solution as electrolyte, platinum sheet as counter electrode, Hg / HgO as reference electrode, and FeCoNiCuMoOx as working electrode. The material was reconstructed into FeCoNiCuMoOOH by 10 voltammetric cycles (CV) in the voltage range of 0.476-4.076V vs. Hg / HgO.

[0044] Example 6

[0045] The preparation method of a high-entropy hydroxyl oxide for water electrolysis has the following steps:

[0046] Step (1): 4 mmol ferric chloride hexahydrate, 4 mmol cobalt nitrate hexahydrate, 4 mmol nickel nitrate hexahydrate, 4 mmol copper nitrate trihydrate, and 5 mmol citric acid monohydrate were added to a mixed solution of water and ethanol (V / V = 15 ml / 15 ml). Under vigorous stirring, 20 ml of an aqueous solution of 4 mmol sodium molybdate dihydrate was added, followed by transfer to a hydrothermal reactor and incubation at 160 °C for 18 hours. After cooling to room temperature, the solution was washed and dried to obtain FeCoNiCuMoOx.

[0047] Step (2): The FeCoNiCuMoOx obtained in step (1) was subjected to electrochemical treatment. A three-electrode system was formed with 1 M KOH solution as electrolyte, platinum sheet as counter electrode, Hg / HgO as reference electrode, and FeCoNiCuMoOx as working electrode. The material was reconstituted into FeCoNiCuMoOOH after 15 voltammetric cycles (CV) in the voltage range of 0.476-4.076V vs. Hg / HgO.

[0048] Example 7

[0049] The preparation method of a high-entropy hydroxyl oxide for water electrolysis has the following steps:

[0050] Step (1): 4 mmol ferric nitrate nonahydrate, 4 mmol cobalt nitrate hexahydrate, 1 mmol nickel sulfate hexahydrate, 4 mmol copper nitrate trihydrate, and 10 mmol citric acid monohydrate were added to a mixed solution of water and ethanol (V / V = 15 ml / 15 ml). Under vigorous stirring, 20 ml of an aqueous solution of 4 mmol sodium molybdate dihydrate was added, followed by the addition of 3 cm × 5 cm nickel foam. The solution was then transferred to a hydrothermal reactor and maintained at 120 °C for 36 hours. After cooling to room temperature, the solution was washed and dried to obtain FeCoNiCuMoOx / NF.

[0051] Step (2): The FeCoNiCuMoOx / NF obtained in step (1) was subjected to electrochemical treatment. A three-electrode system was formed with 6 M KOH solution as electrolyte, platinum sheet as counter electrode, Hg / HgO as reference electrode, and FeCoNiCuMoOx / NF as working electrode. The material was reconstructed into FeCoNiCuMoOOH / NF by 80 voltammetric cycles (CV) in the voltage range of 0.3-0.8V vs. Hg / HgO.

Claims

1. A high-entropy hydroxyl oxide for water electrolysis, wherein a co-hydroxyl oxide of Fe, Co, Ni, Cu and Mo with a thickness of 0.3-1.0 μm is prepared by hydrothermal deposition coupled with electrochemical reconstruction. The specific steps of the hydrothermal deposition coupled with electrochemical reconstruction preparation method are as follows: Step (1): A certain amount of iron salt, cobalt salt, nickel salt, copper salt, and citric acid are added to a mixed solution of water and ethanol. An aqueous solution of molybdate is then added while stirring. The solution is then transferred to a hydrothermal reactor and kept at 120-160℃ for 18-36 hours. After cooling to room temperature, the solution is washed and dried to obtain powdered molybdenum-based composite oxide, named FeCoNiCuMoOx. The main components of the molybdenum-based composite oxide include: Fe2(MoO4)3, Co2Mo3O8, NiFe2O4, Cu2O and Fe3O4; Step (2): The molybdenum-based composite oxide obtained in step (1) is subjected to electrochemical treatment using a strongly alkaline solution as the electrolyte, and a voltage of 1.4-5 V or higher than 10 mA cm⁻¹ relative to the reversible hydrogen electrode is applied. -1 The current density is maintained for a certain time, and the molybdenum-based composite oxide is electrochemically reconstructed into a high-entropy hydroxy oxide, named FeCoNiCuMoOOH; the molar ratio of iron salt, cobalt salt, nickel salt, copper salt, and molybdate is equal or one of them is in excess / deficient by 20%, and the molar amount of citric acid accounts for 20-40% of the total molar amount.

Citation Information

Patent Citations

  • Metal oxyhydroxide catalyst, electrode, preparation methods of catalyst and electrode and electrochemical electrolysis unit

    CN106693978A

  • Method for preparing single-layer porous cobalt oxyhydroxide nanosheet by adopting electrochemical oxidation method

    CN110364365A

  • Homogeneously dispersed multimetal oxy-hydroxide catalysts

    US20170218528A1